Skin necrosis in COVID-19 patients: complication of therapy or one of clinical and pathological mechanisms of viral infection? - Abbas, Walaa Fadhil; Borisovna, Tamrazova Olga; Vladimirovich, Molochkov Anton; Sergeevna, Stadnikova Antonina (International Journal of Research in Dermatology, 2022)
The coronavirus disease 2019 (COVID-19) is an acute respiratory disease caused by a novel coronavirus (SARS-CoV-2, previously known as 2019-nCoV). Dermatological disorders are among the numerous observations in COVID-19 patients that are consistently reported from various clinical sites throughout the world, although their relationship with illness severity is unknown. Urticarial rash, maculopapular or morbilliform rash, papulovesicular lesions, chilblain, livedo reticularis, vasculitis-like picture, and skin necrosis have all been reported with different frequencies and associated circumstances. In this review article, we will highlight reports of skin necrosis, one of the rare skin findings that are associated with COVID, and their clinical and pathophysiological aspects, in addition to attempting to determine whether they are one of the possible outcomes of this virus infection or a complication of various treatment programs. and to discuss the overlap between skin necrosis due to COVID-19-associated coagulopathies and disseminated intravascular coagulation. Cutaneous necrosis in COVID-19 patients during the pandemic period, according to this review, is not rare. possibly It is simple to diagnose and recognize this dermatological condition, but determining the causal variables and their function in pathogenesis is a complex and difficult task. It’s also tough to categorize because it affects people of all ages, regardless of gender, ethnicity, or health status. All hypotheses discuss the direct viral role, the immune system’s hyperinflammatory state with cytokine storm, the hypercoagulable state with vasculitis, anticoagulant therapy complications, and deep secondary necrotizing infections as possible interactions that lead to necrosis, which can result in serious outcomes such as disseminated intravascular coagulation if not properly treated.